Analisis Produktivitas Kerja dan Biaya dalam Perancangan Alat Pakan Ikan Otomatis pada Tambak Lele - Satya, Rafi Arya Lingga; Murnawan, Hery (Fakultas Teknik Universitas Tulang Bawang, 2025)
Catfish farming (Clarias sp.) is a potential aquaculture sector in Indonesia with high economic value and increasing market demand. However, the farming process faces challenges, such as fish mortality often caused by unequal fish sizes due to uneven feed distribution. This issue is also experienced by UD. Kurnia Tani, a small-medium enterprise in Magetan, which still employs a manual feeding system. This system triggers competition among fish, leading to economic losses and reduced survival rates. This study aims to design an automatic feeding device to improve feeding efficiency and productivity in catfish farming. The design results indicate that the device reduces the required workforce from two to one person and shortens feeding time from eight minutes to four minutes per pond. Additionally, the device increases work productivity by 50% and lowers the cost of production from IDR 17,760 to IDR 11,760. With an investment cost of IDR 2,640,000, the device has a payback period of two months. The automatic feeding device is expected to be an innovative solution to support more efficient and sustainable catfish farming. Keywords: Cost Of Goods Sold, Payback Period, Work Productivity Analysis.